2019
DOI: 10.1016/j.jnt.2019.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Computing the endomorphism ring of an ordinary abelian surface over a finite field

Abstract: We present a new algorithm for computing the endomorphism ring of an ordinary abelian surface over a finite field which is subexponential and generalizes an algorithm of Bisson and Sutherland for elliptic curves. The correctness of this algorithm only requires the heuristic assumptions required by the algorithm of Biasse and Fieker [2] which computes the class group of an order in a number field in subexponential time. Thus we avoid the multiple heuristic assumptions on isogeny graphs and polarized class group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…if End Fq (A) contains the ring of integers of the maximal totally real subfield of Q(π); see [3,Lemma 4.4]. Many recent results in the algorithmic study of abelian varieties over finite fields have productively focused on the case of maximal real multiplication, including results on point counting [1,6], isogeny graphs [3,8,13], and endomorphism ring computation [16]. At the other extreme, Centeleghe and Stix have shown that the minimal order Z[π, π] is also always Gorenstein, where π is a Weil integer [4,Theorem 11].…”
Section: Introductionmentioning
confidence: 99%
“…if End Fq (A) contains the ring of integers of the maximal totally real subfield of Q(π); see [3,Lemma 4.4]. Many recent results in the algorithmic study of abelian varieties over finite fields have productively focused on the case of maximal real multiplication, including results on point counting [1,6], isogeny graphs [3,8,13], and endomorphism ring computation [16]. At the other extreme, Centeleghe and Stix have shown that the minimal order Z[π, π] is also always Gorenstein, where π is a Weil integer [4,Theorem 11].…”
Section: Introductionmentioning
confidence: 99%